2006
DOI: 10.1108/13639510610648502
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of police services using SERVQUAL

Abstract: The purpose of this paper is to explore the application of the SERVQUAL approach to assess the quality of service of Strathclyde Police in Scotland. Measuring service quality in public services is fraught with difficulty especially in public services where customers are vulnerable citizens whose contact with the service may be limited. The paper reports on a SERVQUAL survey of elected representatives serving the area covered by Strathclyde Police Force. The survey captures respondents' expectations of an excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 8 publications
2
64
1
5
Order By: Relevance
“…Thus it can be extrapolated from such perspective that customer satisfaction is among the many core values of the policing in Jamaica. It is well documented in the literature where customer satisfaction or dissatisfaction has been measured using SERQUAL [32,33,43,44,66,[80][81][82][83][84][85][86][87][88], and the issue has also been evaluated in policing in other jurisdictions outside of Jamaica [22,65,89]; yet no such empirical work has been conducted on the Jamaica Constabulary Force (JCF) [24]. The JCF desires to change its image and so it recognizes that customer satisfaction will be critical to which he has included in the 2015-2018 (Appendix C), Corportate Plan [21]; suggesting that service quality is of importance and is long outstanding it the customer service apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it can be extrapolated from such perspective that customer satisfaction is among the many core values of the policing in Jamaica. It is well documented in the literature where customer satisfaction or dissatisfaction has been measured using SERQUAL [32,33,43,44,66,[80][81][82][83][84][85][86][87][88], and the issue has also been evaluated in policing in other jurisdictions outside of Jamaica [22,65,89]; yet no such empirical work has been conducted on the Jamaica Constabulary Force (JCF) [24]. The JCF desires to change its image and so it recognizes that customer satisfaction will be critical to which he has included in the 2015-2018 (Appendix C), Corportate Plan [21]; suggesting that service quality is of importance and is long outstanding it the customer service apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…including unprofessional conduct, a study has never been conducted on service quality using SERVQUAL on the JCF; yet the police speak of consumer satisfaction among its core values in the 2015-2018 Corporate Plan [20,21]. The issue of measuring service quality, using SERVQUAL, has been done in other police jurisdiction [22,23]. Neither a review of the JCF by Herst [13] nor JCF manual [24] did not speak to an evaluation of the quality of service of the organization.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary, the customer expectations is determined by responsiveness and assurance. Donnelly et al (2006) conducted a research in Strathclyde Police in Scotland to explore SERVQUAL Model. He reported that a service quality expectation is perceived a good understanding by their customers.…”
Section: Service Quality In the Public Servicementioning
confidence: 99%
“…The clients are becoming less loyal to one business entity and are looking for new business entities which are able to better satisfy their needs. Yan Yeung et al (2006) have argued that, nowadays, the practice of outsourcing the logistics services to third parties is continuously increasing; therefore, it is particularly important for the third parties to deliver these services properly (Lee 2005;Kang 2006;Seth et al 2006;Donnelly et al 2006;Ismail et al 2006;Pantouvakis 2008;Lonial et al 2010;Kersten, Koch 2010;Juga et al 2010;Rodrigues et al 2011;Banomyong 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is highly important for the service provider to know what the client expects whereas the client must be sure that the service provider is aware of the expectations (Parasuraman 1998;Donnelly 2006;Seth 2006;Busacca 2005;Gilbert 2006). has pointed out that, considering the client's time, expenditures, resources and etc., it is more convenient to receive the whole complex of logistics services from one company than to order them from different companies.…”
Section: Introductionmentioning
confidence: 99%